2020
DOI: 10.2174/1573405615666191111142039
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Primary Auditory Cortex in the Characterization of Autism Spectrum in Young Adults using Brain Connectivity Parameters and Deep Belief Networks: An fMRI Study

Abstract: Background: The spectrum of autism includes High Functioning Autism(HFA)and Low Functioning Autism(LFA). Brain mapping studies have revealed that, the autism individuals have overlaps in brain behavioural characteristics. Generally, the high functioning individuals are known to exhibit higher intelligence and better language processing abilities. However, the specific mechanisms associated with the functional capabilities are still under research. Objective: This paper attempts to address the overlapping p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…There are literature suggesting significant differences in brain behavior among low and high-functioning autistic children utilizing fMRI. 49 Srinivasan et al used a procedure based on language processing capacities to distinguish autism spectrum disorders (LFA and HFA) utilizing functional connectivity patterns and brain connectivity characteristics. The study reported a significant measurable difference in EEG functional connectivity metrics between the two groups.…”
Section: Discussionmentioning
confidence: 99%
“…There are literature suggesting significant differences in brain behavior among low and high-functioning autistic children utilizing fMRI. 49 Srinivasan et al used a procedure based on language processing capacities to distinguish autism spectrum disorders (LFA and HFA) utilizing functional connectivity patterns and brain connectivity characteristics. The study reported a significant measurable difference in EEG functional connectivity metrics between the two groups.…”
Section: Discussionmentioning
confidence: 99%
“…The finding that hypomyelination leads to reduced PV + neuron density but normal density of VVA + cells is remarkably similar to what has been reported for several mutant mice that display autism spectrum disorder (ASD) endophenotypes, that is, PV +/− , Shank1 −/− and Shank3B −/− mice (Filice et al, 2016 ). Interestingly, myelin defects have been found in ASD patients (Graciarena et al, 2018 ; Steinman & Mankuta, 2019 ), which also display auditory processing deficits (Jones et al, 2020 ; Rotschafer, 2021 ; Srinivasan et al, 2020 ). Together, these observations raise the possibility that defects in myelination might contribute to some aspects of ASD by their negative impact on inhibitory networks.…”
Section: Discussionmentioning
confidence: 99%
“…The finding that hypomyelination leads to reduced density of PV + neurons but normal density of VVA + cells is remarkably similar to what has been reported for several mutant mice that display autism spectrum disorder (ASD) endophenotypes, i.e., PV +/- , Shank1 -/- and Shank3B -/- mice (Filice, Vorckel, Sungur, Wohr, & Schwaller, 2016). Interestingly, myelin defects have been found in ASD patients (Graciarena, Seiffe, Nait-Oumesmar, & Depino, 2018; Steinman & Mankuta, 2019), which also display auditory processing deficits (Jones et al, 2020; Rotschafer, 2021; Srinivasan, Udayakumar, & Anandan, 2020). Together, these observations raise the possibility that defects in myelination might contribute to some aspects of ASD by their negative impact on inhibitory networks.…”
Section: Discussionmentioning
confidence: 99%